Effect of compaction method on pore pressure development - Teeracharti Ruenkrairergsa; Moh, Za-Chieh; Mackey, Robert D.; Chai Muktabhant (Bangkok : Asian Institute of Technology, 1968)
This thesis presents the results of an investigation on the pore pressure and shearing characteristics of compacted Bangkok Clay. The stress-strain properties were determined by the use of the triaxial testing apparatus, and consolidated undrained compression tests with pore pressure measurement were utilized. Three methods of compaction, i.e. dynamic, static, and kneading were employed in the study. Specimens were compacted at three different water content. The test results show that both the compaction method and the molding water content have significant effect on the pore pressure development and the stress-strain characteristics of compacted Bangkok Clay. The strength of specimens prepared at the same molding water content were in the descending order as static, dynamic, and kneading. The excess pore pressure developed were in the descending order as kneading dynamic, and static. Specimens prepared at water content dry of optimum generally yielded higher strength and lower excess pore pressure than those compacted at wet of optimum water content (by the same compaction method)
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1968
Keywords: Clay -- Thailand -- Bangkok